Continental philosophy: A very short introduction - Critchley, Simon (Oxford Oxford university press, 2001)
In this enlightening new Very Short Introduction, Simon Critchley shows us that Continental philosophy encompasses a distinct set of philosophical traditions and practices, with a compelling range of problems all too often ignored by the analytic tradition. He discusses the ideas and approaches of philosophers such as Kant, Hegel, Nietzsche, Husserl, Heidegger, Sartre, Habermas, Foucault, and Derrida. He also introduces key concepts such as existentialism, nihilism, and phenomonology, by explaining their place in the Continental tradition.